2015
DOI: 10.1007/s12687-015-0238-0
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic analysis in the clinic: benefits and challenges for health care professionals and patients in Brazil

Abstract: Despite significant advances in the diagnosis and treatment of genetic diseases in the last two decades, there is still a significant proportion where a causative mutation cannot be identified and a definitive genetic diagnosis remains elusive. New genome-wide or high-throughput multiple gene tests have brought new hope to the field, since they can offer fast, cost-effective and comprehensive analysis of genetic variation. This is particularly interesting in disorders with high genetic heterogeneity. There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
0
20
0
1
Order By: Relevance
“…In January 2014, through Ordinance 199, the Ministry of Health introduced and approved the National Policy for Rare Diseases within the SUS, which encompasses some aspects of the NPCCCG assessed in this study. An important contribution of the policy is the need to train professionals to perform GC (Brazil, 2014;Lima & Horovitz, 2014;Ashton-Prolla et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In January 2014, through Ordinance 199, the Ministry of Health introduced and approved the National Policy for Rare Diseases within the SUS, which encompasses some aspects of the NPCCCG assessed in this study. An important contribution of the policy is the need to train professionals to perform GC (Brazil, 2014;Lima & Horovitz, 2014;Ashton-Prolla et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve this goal, healthcare professionals require a basic knowledge of genetic principles and the ability to integrate genomics into their daily clinical practice (Thompson & Brooks, 2011;Boyes, 2013;Umberger et al, 2013;Seven et al, 2015). In Brazil, the need has been recognized to structure the Unified Health System (SUS)a network of regionalized and hierarchical servicesto provide comprehensive care in clinical genetics (Brazil, 2009;Lopes-Júnior et al, 2014a;Passos-Bueno et al, 2014;Ashton-Prolla et al, 2015). In 2009, Brazil's Ministry of Health proposed a plan of action to pursue this challenge (Brazil, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical aspects are one of the main challenges of WES/WGS due to incidental findings, such as the identification of pathogenic mutations in genes not related to the main investigation [119]. Careful consideration will also need to be given to variants of unknown significance (VUS), identified through NGS.…”
Section: Molecular Genetics Analysesmentioning
confidence: 99%
“…Finally, genomic analysis for the early identification of tailored therapy for cancer patients has been made possible with the development of the Cancer Genome Atlas (TCGA) 1 . We envision that TCGA and COSMIC databases will revolutionize cancer patient diagnosis and treatment (Ashton-Prolla et al, 2015). This is already being realized in the MOSCATO trial where druggable genomic aberrations were identified and targeted in patients (Massard et al, 2017).…”
Section: Genomicsmentioning
confidence: 99%